Comparação de desfechos clínicos de pacientes incidentes em diálise peritoneal provenientes dos programas de transplante renal ou tratamento conservador - Costa, Laurisson Albuquerque Da [UNIFESP] (2019)
Objectives: To compare the occurrence of mortality, technique failure and peritonitis among incident patients in PD coming from either Tx or pre-dialysis treatment. Methodology: A retrospective study in which 47 adult patients with Tx failure (Tx group) were matched for age, gender, diabetes mellitus (DM) and, modality and start year of PD, with 1:1 predialysis patients (nTx group). The Fine-Gray competing risk model was used to analyze mortality and technique failure. Results: Compared to nTx, Tx group had a lower body mass index, serum potassium and albumin concentrations and a higher ferritin level, transferrin saturation and number of patients with positive serology for viral hepatitis. There was a trend to a higher number of deaths in the Tx group (23 vs 9%; p=0.09) with infection as the main cause of death. In the multivariate analysis, patients of Tx group had 4.4-times higher risk of death (p=0.007). The number of patients with technique failure was similar in both groups (40 vs 38%; Tx vs nTx group, respectively; p=0.83), with peritonitis as the main cause of failure in both groups. In the multivariate analysis, prior Tx was not associated with an increased risk of technique failure. The number of patients with peritonitis did not differ between groups (62 vs 43%; Tx vs nTx ; p=0.63), and a trend towards a higher incidence density of peritonitis was found in the Tx group (0.59 vs 0.40 episodes/patient/year; p=0.06). The time to the first episode of peritonitis was similar (p=0.73), as well as the identified microorganisms (p=0.68). Conclusion: Previous Tx is a risk factor for mortality but not for technique failure or peritonitis in patients on a PD program.